Adaptasi Ekonomi Nelayan Melalui Pengelolaan Hasil Tangkapan dan Diversifikasi Pendapatan Keluarga - Soendra Kurnia Ilaihi; Eni Apriliyana; Yusril Maulana Ma'arif; Muhammad Iqbal Pratama Sanax; Mulawarman Mulawarman (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Economic pressures resulting from environmental degradation and structural changes have significantly affected the sustainability of traditional fishing livelihoods in the Nongsa coastal area of Batam. This study investigates the economic adaptation strategies adopted by traditional fishermen in response to declining fish catches, rising fuel prices, and limited government support. A qualitative approach was employed through in-depth interviews and field observations involving local fishing communities. The findings indicate that coastal households have increasingly diversified their livelihoods, with only 5–10 of approximately 270 households continuing to depend primarily on capture fisheries. Adaptation strategies include the development of floating net cage aquaculture, the provision of marine tourism services, and participation in fishermen’s cooperatives to strengthen collective economic capacity. These strategies have reduced dependence on capture fisheries while creating alternative sources of income and improving community resilience. However, their effectiveness remains constrained by limited institutional support, access to capital, and sustainable coastal management policies. Strengthening cooperative institutions, expanding livelihood diversification, and improving government assistance are therefore essential to enhancing the long-term economic resilience of coastal communities facing environmental and socioeconomic challenges.